COMBINING RESISTANCE TO LATE BLIGHT AND PVY IN POTATO - Bhardwaj, Vinay; Kaushik, S K.; Chakrabarti, S. K.; Pandey, S K; Singh, P H.; Manivel, P.; Singh, B. P. (Potato Journal, 2013)
An attempt was made to develop potato hybrids with combined resistance to late blight and potato virus Y. Five crosses were made between the late blight resistant (PVY susceptible-nulliplex) and PVY resistant (duplex, late blight susceptible) parents and progenies were screened for both the diseases. The present study reveals that there is ample scope to combine high yield with late blight and PVY resistance in potato.